Re-powering the Nature-Intensive Systems: Insights From Linking Nature-Based Solutions and Energy Transition - Razzaghi Asl, Sina (Frontiers in Sustainable Cities, 2022)
Nature-based and energy transition strategies are amongst most considerable solutions that are gaining popularity in recent years, especially in global north. This review provides a new approach to link these apparently independent concepts to highlight the potentials of coupled systems. Exploring common boundary concepts such as energy infrastructure, natural capital, land sink, ecosystem services etc. in both energy and environmental geography fields can facilitate our understanding toward potential contributions of nature-based solutions and energy transition for efficiency and sustainability goals. The results of this review can help to further develop robust coupled systems to deal with urban societal and environmental challenges such as land and energy scarcity. This review presents a variety of theoretical foundations and the rationales behind nature-based solutions and energy transition including socio-technical transitions, socio-ecological-technological, land-energy transition, and circular economy scholarships. Finally, by proposing future research directions, the role of each boundary concept in coupled NbS-ET systems is shown.